European integration and peripherality: are there lessons from Ireland? - Holger Görg; Frances P. Ruane (Trinity College, Department of Economics, 1999)
This paper suggests that the process of economic integration can generate positive effects for peripheral economies by increasing their attractiveness as a production base for multinational companies. Such investment is likely in the case of goods for which transportation costs are relatively low. Our analysis shows that US investment in Ireland illustrates this process, having increased considerably after 1992, in particular in the "weightless" electronics sector. It shows, however, that other peripheral countries in the EU, namely Greece, Portugal and Spain, have not been successful in attracting a proportionate share of the increased US investment following the process of integration. This suggests that economic integration may be a necessary, but not a sufficient condition for a peripheral country to attract MNCs; other variables such as language and culture, industrial policy and developing agglomerations also count.
Keywords: F15; F20; F23; 330; Europäische Integration; Peripheres Gebiet; Irland; EU-Staaten